About some orders in language and text - Sobczykowa, Joanna (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The subject of the present observations is the phenomenon of the list, a form of notation resulting from acts of ordering of language or of a text. The argument presented in this article focuses upon three examples of listings, illustrating the evolution of the phenomenon at three different stages of the development of oral and written language: 1) the register in the 16th century print edition of the Bible; 2) the manuscript of an ancient diagram explaining relations in the structure of the text of the four gospels; 3) self-registration of the earliest words (holophrases) in children’s speech.